2001
DOI: 10.1002/1521-3765(20011203)7:23<5094::aid-chem5094>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Selective Encapsulation of Chloride Ions within Novel Cage Host Complexes in the Presence of Equimolar Amounts of Chloride and Bromide Ions

Abstract: Four macrotricyclic cage hosts which feature four positive binding sites oriented toward the center of the intramolecular cavity are presented as promising candidates for anion receptors and they have been expected to play a important role in the selective encapsulation of the halide ion Cl- or Br . The complementarity between a macrotricyclic quaternary ammonium ion and Cl- was achieved by fine-tuning of the four ammonium nitrogen atoms and the endocyclic methylene groups. The cage hosts [R4N4(C5H10)4(C6H12)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
3
12
0
1
Order By: Relevance
“…These investigations extent our work on ions and complexes at LLIs 18–21. Interestingly, it was reported that L 4+ derivatives with R = CH 2 ϕ form two‐dimensional assemblies at the interface between the NaCl(001) surface and water where they complex chloride anions 10. This suggests that the host can approach sufficiently close to the water surface to interact with the salt, i.e., that the hosts are “attracted by the interface,” unlike small hydrophilic ions which are “repelled” by the water surface 22.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…These investigations extent our work on ions and complexes at LLIs 18–21. Interestingly, it was reported that L 4+ derivatives with R = CH 2 ϕ form two‐dimensional assemblies at the interface between the NaCl(001) surface and water where they complex chloride anions 10. This suggests that the host can approach sufficiently close to the water surface to interact with the salt, i.e., that the hosts are “attracted by the interface,” unlike small hydrophilic ions which are “repelled” by the water surface 22.…”
Section: Introductionsupporting
confidence: 53%
“…Two modifications of the complex were performed, to reduce its hydrophilicity and to test the resulting interfacial behavior. First, the four exo NMe groups were replaced by NCH 2 ϕ groups ( B system), as in the compounds studied experimentally 9, 10. After 1 ns of dynamics, this CH 2 ϕ– L 4+ analog was also on the average at the surface of water, but closer to the interface (at 1.3 ± 1.2 Å), oscillating between the water side and the chloroform side (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising candidate to meet these criteria is the quaternized adamanzane derivative 3 (Scheme 1), which builds upon a variety of congeners [11][12][13][14] of proven utility in anion complexation. [15][16][17][18][19] Common to all members in this family is the mechanism of anion encapsulation, which rests on the strong Coulombic force resulting from the overlay of four positive charges.…”
mentioning
confidence: 99%
“…Ein Wirt, der diese Kriterien potentiell erfüllen kçnnte, ist das quaternäre Adamanzan 3 (Schema 1), für das mehrere Analoga [11][12][13][14] eine respektable Bindungsstärke für Anionen vorweisen kçnnen. [15][16][17][18][19] Allen Mitgliedern dieser Familie ist ein Einschlussprozess als Bindungsmodus gemeinsam, der auf der starken Coulomb-Anziehung durch Überlagerung von vier positiven Ladungen gründet.…”
unclassified